Not to forget: archival practices in the works of Rosângela Rennó and Éder Oliveira: práticas de arquivos nas obras de Rosângela Rennó e Éder Oliveira - Leite, Everton Cardoso; Oliveira, Matheus Guilherme de (Farol, 2023)
The text deals with narrative in the practices of artists who work with archives, such as Rosângela Rennó and Éder Oliveira. Through their practices, we weave discussions about marginalized layers of society, necropolitics, erasures, identities and appropriation of images. In order to better understand the use of narratives and archives, we established a relationship with the works of Hélio Oiticica and the 3NOS3 Group. For reflection, we bring concepts of memory, archive, art and violence, based on the writings of Walter Benjamin, Ecléa Bosi, Susan Sontag, among others.